Learning Basic Addition Facts Through Sense-Making And Understanding - Poon , Cheng Yong; Yeo , Kee Jiar; Ahmad Zanzali, Noor Azlan (Penerbit Universiti Sains Malaysia, 2014)
The traditional diagnostic and remedial approaches which are based on the behaviourist framework of learning might not facilitate students in acquisition of conceptual understanding and procedural knowledge. This research was intended to help students with mathematics learning difficulties improving their mathematical knowledge of basic addition facts through an instructional model for remedial intervention of mathematics. This model involves application of concrete materials, application of a mixed instructional approach, delivery of conceptual and procedural knowledge, and use of problem-solving activity. Using a case study design, a remediation class teacher and four students at a suburban elementary school were involved. Data was collected using observation, students’ work, and interview. Qualitative data was analysed using a qualitative approach. Research findings indicate that concrete materials could be used as a tool for sense-making or counting by students. It depends on the individual differences of students and the instructional approach of teacher. In general, a teacher-directed learning process was carried out but because students were allowed to make their decisions in problem-solving, some students managed to construct their knowledge rather than follow procedures prescribed by their teacher. Learning of both conceptual and procedural knowledge was facilitated through problem-solving activity and incorporation of some constructivist approaches. Mathematical knowledge of students was improved in the remedial intervention which was based on the instructional model. For remedial intervention, teachers should reduce the use of behaviourist approaches gradually, and incorporate more student centred approaches, based on the student individual differences and usual practice.